2011
DOI: 10.1111/j.1469-0691.2010.03231.x
|View full text |Cite
|
Sign up to set email alerts
|

Skull-base osteomyelitis: fungal vs. bacterial infection

Abstract: Skull-base osteomyelitis (SBO) occurs secondary to invasive bacterial and fungal infection. Distinguishing between fungal and bacterial aetiologies of SBO has significant therapeutic implications. An 18-year (1990-2007) retrospective review of patients with SBO presenting to Westmead Hospital was performed. Epidemiological, clinical, laboratory and radiology data were collated. Twenty-one patients (median age 58 years) with SBO were identified: ten (48%) had bacterial and 11 (52%) had fungal SBO. Diabetes mell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
103
0
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(111 citation statements)
references
References 23 publications
1
103
0
7
Order By: Relevance
“…Focal bone lysis, sequestrum formation, T1 hypointensity and T2 hyperintensity of bone marrow, and adjacent soft tissue infiltration are the most common imaging findings (17). Although skull base osteomyelitis can result from direct invasion by IFS itself, its possibility as the cause of the extrasinonasal infiltrative process in our series seems to be low because it carries much worse prognosis than bacterial skull base osteomyelitis (16).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Focal bone lysis, sequestrum formation, T1 hypointensity and T2 hyperintensity of bone marrow, and adjacent soft tissue infiltration are the most common imaging findings (17). Although skull base osteomyelitis can result from direct invasion by IFS itself, its possibility as the cause of the extrasinonasal infiltrative process in our series seems to be low because it carries much worse prognosis than bacterial skull base osteomyelitis (16).…”
Section: Discussionmentioning
confidence: 90%
“…In our study, diabetes was observed in five of seven patients (71%) with presumed skull Extrasinonasal infiltrative process associated with a sinonasal fungus ball • 351 (28,29). Skull base osteomyelitis usually occurs secondary to infection of the ear or paranasal sinus, especially sphenoid sinus (16,17). Focal bone lysis, sequestrum formation, T1 hypointensity and T2 hyperintensity of bone marrow, and adjacent soft tissue infiltration are the most common imaging findings (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,5 Cranial nerve palsies can occur and have been reported in close to half the patients in some series. 3,5,11 Cranial nerve VII is the most commonly affected but cranial nerves IX, X, XI and XII can also be involved. 12 This is thought to occur due to the infection traversing the fissures of Santorini and the tympanomastoid suture to the Haversian system of the compact bone, and finally to the skull base.…”
Section: -10mentioning
confidence: 99%
“…So, there has been increasing search for green inhibitors. Recently, there are several studies carried out on the use of drugs as inhibitors [5][6][7][8][9][10][11]. The drugs are biocompatibility in nature, environmentally acceptable, readily available and a renewable source.…”
Section: Introductionmentioning
confidence: 99%